Effects of Aquatic Species on Gastrointestinal Digestibility of Allergen Tropomyosin - Yaru LI; Hongwei LUAN; Wenjiao LI; Ying LU (Shipin gongye ke-ji, 2022)
To study the effects of different types of aquatic products and gastrointestinal digestion on tropomyosin (TM), this article selects three crustaceans (Litopenaeus vannamei, Penaeus monodon and Eriocheir sisensis) and two shellfish (Venerupis philippinarum and Sinonovacula constricta) as the research object. Simulated gastric fluid (SGF) and intestinal fluid (SIF) were used to digest the boiled muscles of 5 kinds of aquatic products, the protein composition and immune activity of the subtracted products were analyzed by SDS-PAGE and ELISA. The results showed that all samples were digested faster in SIF, and intestinal was the main place where TM activity was lost. And shellfish (stomach: 86.5%~86.8%, intestine: 90.8%~92.2%) had a significantly better immune activity reduction effect than crustacean aquatic products (stomach: 64.7%~67.7%, intestine: 89.0%~91.5%). By electron microscopy, the myofibrils of crustaceans (156.4~185.8 μm) were significantly longer than that of shellfish (125.0~134.6 μm), and its width was about 3 times that of shellfish. This study found that the type of aquatic products will affect the digestive ability of the gastrointestinal tract of TM. The difference in the muscle tissue structure of crustaceans and shellfish is one of the reasons for the difference in digestibility and immune activity of crustaceans and shellfish. This study can provide a scientific basis for exploring the mechanism of gastrointestinal digestion to reduce the allergenicity of aquatic products.